2012
DOI: 10.5535/arm.2012.36.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Location of Brain Lesion and Cognitive Function and Findings of Videofluoroscopic Swallowing Study

Abstract: ObjectiveTo investigate whether patterns of swallowing difficulties were associated with the location of the brain lesion, cognitive function, and severity of stroke in stroke patients.MethodSeventy-six patients with first-time acute stroke were included in the present investigation. Swallowing-related parameters, which were assessed videofluoroscopically, included impairment of lip closure, decreased tongue movement, amount of oral remnant, premature loss of food material, delay in oral transit time, laryngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 24 publications
2
46
0
2
Order By: Relevance
“…The association of cognitive dysfunction regarding the degree and prognosis of dysphagia with a stroke is well known [293031]. In addition, the relationship between cognitive deficits and dysphagia is significant in other central nervous system diseases such as dementia, mild cognitive impairment (MCI), and Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…The association of cognitive dysfunction regarding the degree and prognosis of dysphagia with a stroke is well known [293031]. In addition, the relationship between cognitive deficits and dysphagia is significant in other central nervous system diseases such as dementia, mild cognitive impairment (MCI), and Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies do not show a relationship between ischemic stroke and dysphagia, describing only suggestive findings of OD after neurological impairment (16,18) . However, several studies have indicated that this type of stroke is the most prevalent in the affected population (19,(22)(23)(24) . Similarly, this was also observed in our study with varying degrees of swallowing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have presented the NIHSS score between 11 and 12 as the cut-off point for risk of dysphagia (10) . The use of the NIHSS is also suggested as an ideal marker in several studies that addressed the consequences of stroke (5,9,10,17,24,29) . Another study assessed the NIHSS score as a predictor for the use of percutaneous endoscopic gastrostomy (PEG) in hospitalized patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the lesion localization as a predictor of dysphagia has recently obtained more interest. While some studies have detected an association between lesion site and dysphagia,[22] others have not found a significant relationship between the location of lesion and presence of dysphagia. [2324]…”
Section: Discussionmentioning
confidence: 99%